2007
DOI: 10.1021/jp075546n
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Atmospheric Chemistry of Methyl Nitrate and Methylperoxy Nitrite. Chemical Mechanisms of Their Formation and Decomposition Reactions in the Gas Phase

Abstract: Potential energy surfaces, minimum energy reaction paths, minima, transition states, reaction barriers, and conical intersections for the most important atmospheric reactions of methyl nitrate (CH(3)ONO(2)) and methylperoxy nitrite (C(3)HOONO) on the electronic ground state have been studied (i) with the second-order multiconfigurational perturbation theory (CASPT2) by computation of numerical energy gradients for stationary points and (ii) with the density functional theory (DFT). The proposed mechanism expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 44 publications
(40 reference statements)
3
30
0
Order By: Relevance
“…The present study not only entirely reproduced the reported isomeric‐conversion and DCs around HOCH 2 NO 2 but also disclosed many other conformers and reaction channels at the levels of B3LYP/6‐31G(d) and B3LYP/6‐311++G(d,p). Related to the chemistry of the atmosphere, many studies were made for methyl nitrate 21 and methylperoxy nitrite 31 , but the isomeric forms and isomerization channels reported were essentially the same as the present study, although some DCs not treated in the present study were shown for radical‐pair processes . A similar result to this study was reported for an isomerization channel between methyl nitrate 21 and methoxy dioxaziridine 45 in connection with the reaction of triplet nitrenes with oxygen .…”
Section: Remarks On the Present Approachsupporting
confidence: 83%
See 3 more Smart Citations
“…The present study not only entirely reproduced the reported isomeric‐conversion and DCs around HOCH 2 NO 2 but also disclosed many other conformers and reaction channels at the levels of B3LYP/6‐31G(d) and B3LYP/6‐311++G(d,p). Related to the chemistry of the atmosphere, many studies were made for methyl nitrate 21 and methylperoxy nitrite 31 , but the isomeric forms and isomerization channels reported were essentially the same as the present study, although some DCs not treated in the present study were shown for radical‐pair processes . A similar result to this study was reported for an isomerization channel between methyl nitrate 21 and methoxy dioxaziridine 45 in connection with the reaction of triplet nitrenes with oxygen .…”
Section: Remarks On the Present Approachsupporting
confidence: 83%
“…As for isomerization routes at high energy regions, rigorous treatments need to be made for deeper understanding. Radical‐pair channels including CH 3 O + NO 2 have been studied in connection with methyl nitrate 21 and methyl peroxynitrite 31 . In some special cases, multi‐reference treatments as well as excited‐surface treatments including conical intersections and seams should also be taken into account.…”
Section: Remarks On the Present Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several theoretical investigations of the energetics and mechanisms of (R1a) and (R1b) . A composite of these energetics is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%